*Changes in the seroepidemiological pattern of Helicobacter pylori infection over the last 10 years in Turkey - Ali ÖZDEN,; Gülendam BOZDAYI,; Muhip ÖZKAN,; S.Kenan KÖSE, (Turkish Journal of Gastroenterology, 2019)
-